Modos de uma professora compreender Modelagem Matemática com apoio exclusivo na literatura - Souza, Nagmar Ferreira de (2022)
Reformulating the teaching of Mathematics, adapting it to the daily life and needs of the student, is a teme of wide discussion. In that regard, it becomes interesting to include different approaches in the curriculum for teaching Mathematics. Among these approaches, Mathematical Modeling in Mathematics Education is a possibility that contributes to the teaching of mathematical content, since it offers students the opportunity to become co-participants and even protagonists in the teaching and learning process. However, in this context, questions arise about the discrepancy between the immense amount of material favorable to Modeling available in the literature and the effectiveness of these practices in the teaching of Mathematics. One possibility, in the search to find ways to answer them, is to try to understand how a teacher autonomously deals with the Modeling material that comes to him. In this sense, we seek to investigate, in a phenomenological posture, the following research question: “What understanding is shown to the teacher when seeking to develop Mathematical Modeling based exclusively on literature?”. For this, the dice of this research were constituted from the experience lived by a teacher who, for the first time, sought to develop Mathematical Modeling with the exclusive support of the literature. All the material produced, the opinions and expressions of feelings experienced were recorded, transcribed and later analyzed. Of this analysis, four categories emerged: a) understandings articulated in dialogue with literature; b) feelings that emerged in the dialogue with the literature and in the implementation; c) procedures for organizing and implementing the Modeling activity; and d) expectations. These categories were interpreted hermeneutically and, thus, revealed, among other things, that it is not literature per se that guides the teacher's action with Modeling, but care. It is he who acts as a guiding axle and takes the teacher, from what is considered in the literature, to ponder and decide what is or is not appropriate for their practice in the classroom and for their students. In addition, the ways of proceeding with the new practice are based on the usual practices, which reveals that understanding always takes place in the fusion of horizons.